8-6x+3x=-8x-3x

Simple and best practice solution for 8-6x+3x=-8x-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-6x+3x=-8x-3x equation:


Simplifying
8 + -6x + 3x = -8x + -3x

Combine like terms: -6x + 3x = -3x
8 + -3x = -8x + -3x

Combine like terms: -8x + -3x = -11x
8 + -3x = -11x

Solving
8 + -3x = -11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11x' to each side of the equation.
8 + -3x + 11x = -11x + 11x

Combine like terms: -3x + 11x = 8x
8 + 8x = -11x + 11x

Combine like terms: -11x + 11x = 0
8 + 8x = 0

Add '-8' to each side of the equation.
8 + -8 + 8x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 8x = 0 + -8
8x = 0 + -8

Combine like terms: 0 + -8 = -8
8x = -8

Divide each side by '8'.
x = -1

Simplifying
x = -1

See similar equations:

| 8n^2/3 | | 3/20=24/x | | 8a-6=66 | | -4x=20/3 | | 4(x+9)=2x-1 | | -8x+4(1+5x)=-6-1 | | .19x+.33=2.04 | | w*6/e=36 | | -2x+39=x+18 | | 3(x-2)=35.7 | | x^2+y^2-8x-4y+3=0 | | -2x-12=-5x-3 | | -3.9x=-11.31 | | 34/50 | | X+3.9=-8.7 | | sqrt(x+1)-2=sqrt(x+3)+x | | 5X+X+y+(y+29)=127 | | 3y+3x=0 | | 3n^2+37n-1360=0 | | 6(s-2)=5(s+10) | | 144=18n+45 | | 14+2(4s-3)=40 | | 3n-7=6n-2n | | 3/9=y/21 | | (8x+100)+(2x+50)=90 | | 6x-7/7x=6=x-3/x-2 | | 5y=4cosx+1 | | 4-7z=22+22 | | 8a^3-27= | | 4s+4t= | | 6x-17=2x+3 | | 8(x-3)=-7(x+2)+47 |

Equations solver categories